SYSTEMATIC LITERATURE REVIEW BASED STUDY OF THE SYNERGY OF NURSING TEAMS TO ENHANCE PATIENTS SAFETY AND QUALITY OF HEALTH CARE TO ACHIEVING SAUDI VISION 2030 - Mohammed Hassan Alhothali, Mohammed Abdu Ali Khurizi, Saeed Mohammad Saeed Alzahrani, Saeed Ali Safar Alzahrani, Talal Eqab Alharthi, Ahmed Abdallah Hmeed Alnassri, Ghada Mohammad Hussain Fallata; Trad Abdulaziz Shaiy Alharthi, Amal Mohammed Abdullah Kabli, Saeed Marouf Saeed Alzahrani, Abdullah Ahmed Ali Alzahrani (Journal of International Crisis and Risk Communication Research, 2024)
Background: As healthcare systems are expected to provide safer, higher quality patient care in the face of rising demands and increasing complex patient needs, nursing team synergy is vital. Improve in nursing collaboration in Saudi Arabia is harmonious with Vision Saudi 2030 to enhance health care standards and outcomes. Buts, to be effective, achieving synergy in nursing teams faces problems of communication, leadership, organization of training and partnership. Aim: This paper reviews the effects of nursing team synergy on patient safety and healthcare quality, including the factors that affect nursing team collaboration within healthcare settings in Saudi Arabia. Method: A review of peer reviewed research articles published from 2020 – 2024 was systematically conducted. Some of the key topics explored were communication in teams, leadership support, role clarity and ongoing training with regards to patient outcomes and reduction of healthcare errors. Results: This review has shown that effective nursing team synergy with strong communication, good leadership, and training contributes largely to patients' safety and quality of healthcare. In Saudi Arabia evidence shows better patient outcomes, decreased error rate and improved staff morale in cohesive nursing teams. Nonetheless, organizational support and common teamwork training towards the country's Vision 2030 goals are lacking. Conclusion: Nursing team synergy is important to achieve healthcare objectives of Saudi Vision 2030 and to encourage collaborative environment that positively affects patient safety and healthcare quality. It is critical that structured communication, leadership support, and role clarity are integrated if we want effective teamwork. It points out the requirement of constant organizational support and training to maintain teamwork in nursing.